Emotional Distress in Song Lyrics of Niki Zefanya's Album Nicole - Saputro, Dwiky Wahyu; Candraningrum, Dewi (Universitas Muhammadiyah Surakarta, 2025)
This research examines the forms and expressions of emotional distress expressed in the lyrics of NIKI Zefanya's songs on the album Nicole (2022) and explores these expressions as a manifestation of the author's mental state. This study also clarifies the reasons for exploring emotional distress as a central theme in this album through Wellek and Warren's (1949) Literary Psychological Approach. The research method used is descriptive qualitative with a focus on literary psychology. Data was collected from twelve song lyrics from Nicole's album, analyzed using the method of close reading and data recording, according with the Interactive Analysis Approach of Miles, Huberman, and Saldaña (2014). This study identifies and explains five main forms of emotional distress: Heartbreak, Longing, Emotional Collapse, Loneliness, and Regret. utilizing the psychology of the author approach. The findings show that emotional distress is a prominent theme, manifested through the concepts of Loss, Regret, and Self-Healing. The lyrics reflect high emotional vulnerability and authenticity, which resonate deeply with the author's personal experiences, growth, and self-healing process. This research contributes to Literary Psychology by utilizing song lyrics as a medium to analyze the author's emotional and mental state as reflected in their creative works. Nicole's album explores not only musically, but also as a documentation of the author's self-expression and mental state thru the thematic approach of emotional distress. The results of this research can be applied in the field of Education, specifically to enhance students' emotional and mental capacity in understanding modern literary works such as song lyrics.